The Diversity of Warehouse Pests on Areca Nuts in the West Sumatera, Indonesia - Mustopha Ahad; Novri Nelly; Muhammmad Makky (JERAMI : Indonesian Journal of Crop Science, 2022)
Areca nut is one of Indonesia’s leading export commodities that must adhere to certain phytosanitary requirements, including being pest-free. It is infested by several types of insect pests during the storage process. Therefore, this study aims to determine the diversity of warehouse pests that infest areca nuts. It was conducted using a survey method at three warehouses of large collectors and exporters of areca nut in the Padang city and the Padang Pariaman regency. The purposive sampling method was adopted to collect samples from three traders' warehouses. Furthermore, the nut was taken diagonally in a pile, namely the corner and center of 1 kg each, and repeated 4 times. The identification key was used to identify 15 insect types from 10 families and 3 orders. The Cryptolestes pusillus, C. ferugineus, and Carpophilus sp. were found with the highest number of individuals in each warehouse. The diversity index of the three warehouses is 1.78, 2.14, and 1.90 indicating a moderate level. Additionally, the similarity index between warehouses shows a high and very high level of species similarity.